If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 5 = -4(2x + -1) Reorder the terms: 2(-3 + x) + 5 = -4(2x + -1) (-3 * 2 + x * 2) + 5 = -4(2x + -1) (-6 + 2x) + 5 = -4(2x + -1) Reorder the terms: -6 + 5 + 2x = -4(2x + -1) Combine like terms: -6 + 5 = -1 -1 + 2x = -4(2x + -1) Reorder the terms: -1 + 2x = -4(-1 + 2x) -1 + 2x = (-1 * -4 + 2x * -4) -1 + 2x = (4 + -8x) Solving -1 + 2x = 4 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -1 + 2x + 8x = 4 + -8x + 8x Combine like terms: 2x + 8x = 10x -1 + 10x = 4 + -8x + 8x Combine like terms: -8x + 8x = 0 -1 + 10x = 4 + 0 -1 + 10x = 4 Add '1' to each side of the equation. -1 + 1 + 10x = 4 + 1 Combine like terms: -1 + 1 = 0 0 + 10x = 4 + 1 10x = 4 + 1 Combine like terms: 4 + 1 = 5 10x = 5 Divide each side by '10'. x = 0.5 Simplifying x = 0.5
| 3-4(x-5)=3x+6(x-3) | | R+48=7c | | Q=7-2p | | 10=4d+2 | | 2.4x+7.2=-62.4 | | 2(-5)-3(3/4)-(6) | | 2lx-6l=48 | | f(x)=x^4-3x^2+5 | | 25x+2y-19x-1y= | | 4x^2+25y^2-50y=75 | | -7.9d+7.7=274.72 | | (-5)(6)(1/3) | | -7d+7.7=274.72 | | 5p-2=3/4 | | -3(x-1)+9=3 | | 5+3h=17 | | (2x-3)+5=-4(2x-1) | | n+23445566776554544=23445566776554544 | | m/-3=2 | | -u+9=32.9 | | T-(-1)=(-5) | | L=-5t^2-8t+120 | | 2X^2+3X+7=2 | | x^2+8x+15=63 | | n-23445566776554544=23445566776554544 | | 3(x-7)-2(2x+4)=7 | | 4x+x+-2x+3=54 | | 7r-3=-309.6 | | 32-6x=11-9x | | 6x^2+1.5x+2=0 | | f/3-15=-12 | | -12h-5g+8-g= |